1994
DOI: 10.1073/pnas.91.25.11777
|View full text |Cite
|
Sign up to set email alerts
|

Latent capacities for gametogenic cycling in the semelparous invertebrate Nereis.

Abstract: Most nereid polychaetes are strictly semelparous, a single episode of reproduction being invariably followed by death. Endocrine manipulation in Nereis diversicolor by the regular inplantation of cerebral ganglia from immature donors unveils characteristics associated with a capacity to engage in repeated gametogenic cycling. Such manipulation permits full maturation ofthe gametes but blocks spawning. Gamete resorption then leads on to another bout of gametogenesis and a new cohort of gametes is formed. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 15 publications
1
10
0
3
Order By: Relevance
“…Declining production of the hormone in the later stages of maturation thus inhibit regeneration and somatic growth but free the processes which are characteristic of the later stages of maturation. Golding and Yuwono (1994) have shown that the deactivated ganglia of submature Nereidae can be reactivated, implying the possibility that an iteroparous mode of reproduction was previously present in the proto-Nereidae. The observations presented in this paper point to a more uniform pattern of endocrine control of reprodution in the various families of the Phyllodocida than had previously been thought to have been possible.…”
Section: Discussionmentioning
confidence: 97%
“…Declining production of the hormone in the later stages of maturation thus inhibit regeneration and somatic growth but free the processes which are characteristic of the later stages of maturation. Golding and Yuwono (1994) have shown that the deactivated ganglia of submature Nereidae can be reactivated, implying the possibility that an iteroparous mode of reproduction was previously present in the proto-Nereidae. The observations presented in this paper point to a more uniform pattern of endocrine control of reprodution in the various families of the Phyllodocida than had previously been thought to have been possible.…”
Section: Discussionmentioning
confidence: 97%
“…In the related species Nereis diversicolor , it could be shown that implantation of ganglia from immature animals into the coelomic cavity of maturing animals, reversed the effects of the decreasing nereidin concentration. In particular, germ cells were resorbed and the ability to regenerate lost segments was re-established (Golding and Yuwono, 1994). These findings highlight the exceptional importance of neuroendocrine signals in semelparous reproduction and suggest that the underlying molecular mechanisms are conserved across different annelids (Hauenschild, 1956b, 1959; Golding, 1967a, 1967b; Durchon and Porchet, 1970; Hofmann, 1976; Cardon et al, 1981; Golding, 1983; Golding and Yuwono, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, germ cells were resorbed and the ability to regenerate lost segments was re-established (Golding and Yuwono, 1994). These findings highlight the exceptional importance of neuroendocrine signals in semelparous reproduction and suggest that the underlying molecular mechanisms are conserved across different annelids (Hauenschild, 1956b, 1959; Golding, 1967a, 1967b; Durchon and Porchet, 1970; Hofmann, 1976; Cardon et al, 1981; Golding, 1983; Golding and Yuwono, 1994).
10.7554/eLife.17126.003Figure 1. Vitellogenin expression in eleocytes is a quantitative measure for the maturation stage of Platynereis , allowing for the establishment of a bioassay to purify the enigmatic brain hormone, nereidin.( A ) Scheme summarising the critical role of the brain hormone nereidin in energy expenditure, as derived from classical experiments: Before maturation (left), high nereidin levels sustain somatic growth, but repress reproduction; drops in nereidin activity levels initiate the generation of germ cells and sexual maturation (right).
…”
Section: Introductionmentioning
confidence: 99%
“…Spawning never occurs, a situation that has occasionally been observed in iteroparous species (Olive et al 1981a). According to Golding and Yuwono (1994), this latent capacity is reminiscent of an iteroparous ancestry and may constitute a preadaptation to return to this condition.…”
Section: The Feedback Substancementioning
confidence: 98%
“…As the level of endocrine activity of a transplanted brain removed from immature donors is maintained for some months after transfer into a host (Golding 1985(Golding , 1987, it is possible to cyclically increase the hormone titer by periodic (bimonthly) intracoelomic implantation of such cerebral ganglia (Golding and Yuwono 1994). When subjected to such experimental conditions, the worms achieve repeated cycles of gametogenesis, each cycle ending with resorption of the gametes, with no spawning.…”
Section: The Feedback Substancementioning
confidence: 99%